The work of Sartre : search for freedom and the challenge of history - Mészáros, István, 1930- (Monthly Review Press, 2012)
This landmark book, first published in 1979, met acclaim as a doubly important work of radical philosophy. Its subject, Jean-Paul Sartre, was among the twentieth century's most controversial and influential philosophers; its author, István Mészáros, was himself establishing a reputation for profound contributions to the Marxian tradition, which would continue into the next century. The Work of Sartre was thus considered essential for its insights on Sartre and as a piece of Mészáros's developing politico-philosophical project. In this completely updated and expanded volume, Mészáros examines the manifold aspects of Sartre's legacy - as novelist, playwright, philosopher, and political actor- and in so doing casts light upon the enture oeuvre, situating it within the historical and social context of Sartre's time. Although critical of aspects of Sartre's philosophy, Mészáros celebrates his unyielding commitment to the struggle against the power of capital, and elucidates what this means for the individual in their search for freedom.